1897 Iowa Code Ann. 1898 - (:unkn) unknown (My University, 1897)
§ 4775: Prohibited concealed carry and brandishing of pistols, revolvers, guns at another. Violators guilty of a misdemeanor and fined not more than one hundred dollars, or imprisoned in the county jail not more than thirty days.
Keywords: BRANDISHING; CARRY - CONCEALED